Срочно !!! Обчисліть
\ frac {x} {x + 2} — \ frac {(x-2) ^ {2}} {2} * (\ frac {1} {x ^ {2

Срочно !!! Обчисліть
\ Frac {x} {x + 2} - \ frac {(x-2) ^ {2}} {2} * (\ frac {1} {x ^ {2} -4} + \ frac {1} { x ^ {2} -4x + 4}) =
повинно вийти без букви

  •  \ frac {x} {x + 2} - \ frac {(x-2) ^ {2}} {2} * (\ frac {1} {x ^ {2} -4} + \ frac {1} {x ^ {2} -4x + 4}) =
    Спочатку обчислимо суму в дужках
     \ frac {1} {x ^ {2} -4} + \ frac { 1} {x ^ {2} -4x + 4} = \ frac {1} {(x-2) (x + 2)} + \ frac {1} {(x-2) ^ 2} = \ frac { x-2 + x + 2} {(x-2) ^ 2 (x + 2)} = \ frac {2x} {(x-2) ^ 2 (x + 2)}
    Далі множимо на дріб
     \ frac {(x-2) ^ {2}} { 2} * \ frac {2x} {(x-2) ^ 2 (x + 2)} = \ frac {x} {x + 2}
    Одержаний результат віднімаємо
    \ Frac {x} {x + 2} - \ frac {x} {x + 2} = 0